Contextualized Araling Panlipunan Instruction and Historical Learning Engagement Among Grade 10 Learners in a Philippine Secondary School Setting - SORIANO, MARIETA (Studies in Technology and Education, 2026)
Contextualized instruction and learner engagement are essential components of meaningful Araling Panlipunan education in secondary schools. This study explored contextualized Araling Panlipunan instruction and historical learning engagement among Grade 10 learners at Saint Paul Vocational and Industrial High School. Anchored on Constructivist Learning Theory and Culturally Responsive Teaching Theory, the study employed a descriptive qualitative research design to examine learners’ classroom experiences, instructional engagement, historical understanding, and participation in Araling Panlipunan instruction. Participants included selected Grade 10 learners and Araling Panlipunan teachers. Data were gathered through semi-structured interviews, focus group discussions, classroom observations, and document analysis. Braun and Clarke’s (2006) thematic analysis approach was utilized in analyzing the gathered data. Findings revealed that contextualized instructional practices, historical storytelling, collaborative discussions, and localized learning activities significantly contribute to learners’ historical understanding and engagement in Araling Panlipunan education. Learners demonstrated greater participation and appreciation of historical concepts when instructional discussions were connected to local culture, community experiences, and contemporary societal issues. The findings further revealed that interactive classroom environments and learner-centered instructional approaches strengthen learners’ critical thinking, communication competence, and reflective understanding of Philippine history and society. However, challenges such as limited instructional resources, passive classroom participation, difficulty understanding abstract historical concepts, and limited exposure to historical materials affected instructional engagement and historical learning experiences. The study concludes that contextualized and culturally responsive instructional practices significantly contribute to meaningful historical learning engagement among Grade 10 learners. Strengthening localized instruction, collaborative learning environments, and interactive historical discussions is recommended to improve learner engagement in Araling Panlipunan education. Keywords: contextualized instruction, Araling Panlipunan, historical learning engagement, learner participation, qualitative research, secondary education, Philippine history